ANALISIS KINERJA PEGAWAI NEGERI SIPIL (Studi Pada Dinas Pendapatan Daerah Kabupaten Kutai Timur) - Sundani, Juniarni Kiki (PREDIKSI, 2016)
This study aims to determine the level of performance of Civil Servants On Revenue Service East Kutai Regency and the factors that affect employee performance. The approach used in this study is a qualitative descriptive approach. The results showed that the assessment of the performance of individual employees have met the standard of individual capabilities so that tasks and work can be done properly. Such capabilities include service orientation, integrity, commitment, discipline, teamwork and leadership, all of which are part of the work behavior. Besides, the working environment is also conducive to support the implementation of the tasks and jobs that are owned by each employee. The results showed also that of the assessment Employee Work Goals (SKP) obtained by the average value of SKP all employees who serve as the respondent is at 88.86, which means the fit in either category. Besides, the value of Conduct Working employees overall average of 86.75, which means that Work Behavior overall employees included in both categories.Â